2021
DOI: 10.1109/access.2021.3097185
|View full text |Cite
|
Sign up to set email alerts
|

Overall Filtering Algorithm for Multiscale Noise Removal From Point Cloud Data

Abstract: The multiscale noise in the 3D point cloud data of rock surfaces which collected by 3D scanners has a significant influence on the exploration of rock surface morphology. To this end, this paper proposes a multiscale noise removal overall filtering algorithm. The specific processing procedure of the algorithm is as follows. First, a weighted principal component analysis is performed on point cloud data, i.e., the neighboring point distance is used as a weight in the principal component analysis, the covariance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…(1) When n z = 0, it means that the structural plane is upright and the tendency does not exist. Its occurrence is generally described by strike According to the above principles, CloudCompare plugin can be used to extract the stable occurrence of rock mass structural plane based on three-dimensional point cloud data [18,19]. Taking an open-pit quarry as an example, the total area of the mining area is about 101,510 m 2 , the maximum elevation of the top of the slope on the slope surface is about +85.0 m, and the elevation of the bottom varies from +5.0 m to +20.0 m. After the field survey, it is found that the natural slope of the mountain in the mining area is about 15 °~25 °, the overall field of vision is wide, and the GPS satellite signal is stable, which is suitable for UAV flight.…”
Section: Extraction Of Rock Mass Structurementioning
confidence: 99%
“…(1) When n z = 0, it means that the structural plane is upright and the tendency does not exist. Its occurrence is generally described by strike According to the above principles, CloudCompare plugin can be used to extract the stable occurrence of rock mass structural plane based on three-dimensional point cloud data [18,19]. Taking an open-pit quarry as an example, the total area of the mining area is about 101,510 m 2 , the maximum elevation of the top of the slope on the slope surface is about +85.0 m, and the elevation of the bottom varies from +5.0 m to +20.0 m. After the field survey, it is found that the natural slope of the mountain in the mining area is about 15 °~25 °, the overall field of vision is wide, and the GPS satellite signal is stable, which is suitable for UAV flight.…”
Section: Extraction Of Rock Mass Structurementioning
confidence: 99%
“…Direct processing of such data could result in significant computational and storage overheads. Therefore, this study employs uniform downsampling algorithm [24] and straight-through filter [25] to streamline the point cloud data after pose adjustment. Following down-sampling and passthrough filtering, the number of points reduces from 3,145,728 to 185,781, markedly reducing the data volume and effectively alleviating the computational burden of subsequent algorithms.…”
Section: Point Cloud Preprocessing and Point Cloud Segmentation 411 P...mentioning
confidence: 99%
“…The presence of numerous noise points in the point cloud obtained by depth camera shooting and ORB-SLAM2 dense mapping, which is a random error, is inevitable because of illumination, obstacles, and sensor errors 21 . The aforementioned point cloud must be filtered to eliminate noise points and outliers to improve the detection accuracy of tunnel deformation and ensure the quality of the subsequent processing, such as point cloud slicing and visualization.…”
Section: Point Cloud Composite Filteringmentioning
confidence: 99%